2001
DOI: 10.4049/jimmunol.167.4.1909
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of RelB in Germinal Center and Marginal Zone Formation and Proper Expression of Homing Chemokines

Abstract: High levels of the Rel/NF-κB family member RelB are restricted to specific regions of thymus, lymph nodes, and Peyer’s patches. In spleen, RelB is expressed in periarteriolar lymphatic sheaths, germinal centers (GCs), and the marginal zone (MZ). In this study, we report that RelB-deficient (relB−/−) mice, in contrast to nfkb1−/−, but similar to nfkb2−/− mice, are unable to form GCs and follicular dendritic cell networks upon Ag challenge in the spleen. RelB is also required for normal organization of the MZ an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
194
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(207 citation statements)
references
References 75 publications
12
194
1
Order By: Relevance
“…RelB and p50, two subunits of the NF-‹ B transcription factor, are required for marginal zone B cell formation [37,38] and may mediate BAFF signaling in that respect.…”
Section: Discussionmentioning
confidence: 99%
“…RelB and p50, two subunits of the NF-‹ B transcription factor, are required for marginal zone B cell formation [37,38] and may mediate BAFF signaling in that respect.…”
Section: Discussionmentioning
confidence: 99%
“…Mice deficient in the non-canonical pathway fail to segregate B-cell-T-cell zones and FDC networks, and they fail to form GCs following immunization. Marginal zone macrophages, which line the border between red and white pulp areas, are also absent or disorganized in RelB, p52, NIK or IKKa knockouts (Franzoso et al, 1998;Weih et al, 2001). Some splenic defects are also attributable to effects on hematopoietic cells.…”
Section: Secondary Lymphoid Organsmentioning
confidence: 99%
“…Indeed, genetic analysis indicated that RelB plays an essential role in lymph node development, especially in maintaining lymph node architecture in adult mice (Weih et al, 2001;Yilmaz et al, 2003). Important lymphoid chemokine genes, such as BLC and SLC, were shown to be RelB target genes (Basak et al, 2008;Schneider et al, 2004) via a proposed variant kappaB site that recruits RelB-but not RelA-containing dimers upon LTβR stimulation (Bonizzi et al, 2004).…”
Section: Non-canonical Activation Of Nf-κb/relb Dna Binding Acitvitymentioning
confidence: 99%